PENERAPAN TEKNOLOGI INFORMASI E-GOVERNMENT SEBAGAI MEDIA KOMUNIKASI PEMERINTAHAN KEPADA MASYARAKAT (Studi Kasus Website E-Government DPRD di Kabupaten Paser Kalimantan Timur) - Ilyasha Anwar, Zulfani; Taufik, Mohammad (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Study of Application of E-Government Information Technology as A Government Communication Medium to The Community (Case Study of The DPRD E-Government Website in Paser Regency, East Kalimantan). This research aims to find out how the application of e-government information technology as a medium of government communication to the public (case study of the DPRD e-Government website in Paser Regency, East Kalimantan) in achieving the efficiency of the successful implementation of e-Government on website media. This study uses a qualitative approach with a descriptive method. The data collection techniques used are semi-structured interviews and documentation. The research informants are the chairman of the Paser Regency DPRD, the operator/admin of the Paser DPRD website manager, related employees, and the community in Paser Regency who know and are involved in the implementation of the Paser Regency DPRD e-Government website media. The results of the study show that based on socialization factors, workflow mechanisms and, community participation, the application of e-Government on website media has not fully run according to the government's goals due to the incomplete media system and lack of public knowledge on the website. Socialization factors, for example, the information and communication department of the DPRD has not conducted socialization directly to the community, so community participation still needs to be increased. In the flow of the website work mechanism, the website manager has not been able to manage the website as a whole, requiring coordination with parties related to website management so that the application of e-government on the website can run as intended.